Money, lies, and God : inside the movement to destroy American democracy - Stewart, Katherine (Bloomsbury Publishing, 2025)
"Why have so many Americans turned against democracy? In this deeply reported book, Katherine Stewart takes us to conferences of conspiracy-mongers, backroom strategy gatherings, and services at extremist churches, and profiles the people who want to tear it all down. She introduces us to reactionary Catholic activists, atheist billionaires, pseudo-Platonist intellectuals, self-appointed apostles of Jesus, disciples of Ayn Rand, women-hating opponents of "the gynocracy," pronatalists preoccupied with the dearth of white babies, Covid truthers, militia members masquerading as "concerned moms" and battalions of spirit warriors who appear to be inventing a new style of religion even as they set about attacking democracy at its foundations. Along the way, she provides a compelling analysis of the authoritarian reaction in the United States. She demonstrates that the movement relies on several distinct constituencies, with very different and often conflicting agendas. Stewart's reporting and comprehensive political analysis helps reframe the conversation about the moral collapse of conservatism in America and points the way forward toward a democratic future."--Amazon.